МАГНИТНОЕ ПОЛЕ ТОКОВ СТАТОРНОЙ ОБМОТКИ СИНХРОННОГО ДВИГАТЕЛЯ С ПОЛЫМ РОТОРОМ - Виштак , Т.В.; Карлов , А.Н.; Кондратенко, И.П.; Ращепкин , А.П. (Інститут електродинаміки НАН України, Київ, 2013)
With respect to the magnetic stirrer of liquid metal in the mold continuous casting machines, made in the form of a synchronous motor with a hollow rotor and excitation system based on permanent magnets, the magnetic field is determined by the stator winding currents. We derive the boundary conditions for the magnetic potential on the surface of the molten metal produced by the stator currents, which are used for the numerical solution of the distribution of magnetic potential in the liquid metal ingot with an arbitrary distribution of its speed. A numerical-analytical method for the determination of the magnetic field in the structural parts of the mold, which is excited by currents of the stator winding. References 2, figure 1.